2000
DOI: 10.1177/01939450022044764
|View full text |Cite
|
Sign up to set email alerts
|

Basic Need Status and Health-Promoting Self-Care Behavior in Adults

Abstract: Health-promoting self-care behavior emphasizing positive lifestyle practices may improve the health and quality of life of adults. One variable that may influence health-related decisions is the status of basic needs as described by Maslow. The purpose of this study was to investigate the relationships among basic need satisfaction, health-promoting self-care behavior, and selected demographic variables in a sample of community-dwelling adults. A convenience sample of 84 community-dwelling adults was recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 31 publications
6
52
0
4
Order By: Relevance
“…The Chinese version of HPLP-II was developed by Wang et al [23], and the reliability and validity have been demonstrated. The HPLP-II instrument contains the following six subscales with total of 52 items: (1) health responsibility (HR, 9 items), (2) spiritual growth (SG, 9 items), (3) physical activity (PA, 8 items), (4) interpersonal relationships (IR, 9 items), (5) nutrition (N, 9 items), and (6) stress management (SM, 8 items). The overall score of HPLP-II was calculated from the mean score of 52 items.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese version of HPLP-II was developed by Wang et al [23], and the reliability and validity have been demonstrated. The HPLP-II instrument contains the following six subscales with total of 52 items: (1) health responsibility (HR, 9 items), (2) spiritual growth (SG, 9 items), (3) physical activity (PA, 8 items), (4) interpersonal relationships (IR, 9 items), (5) nutrition (N, 9 items), and (6) stress management (SM, 8 items). The overall score of HPLP-II was calculated from the mean score of 52 items.…”
Section: Instrumentsmentioning
confidence: 99%
“…A health-promoting lifestyle is a pattern of self-initiated actions which individuals take to control, maintain, or enhance their own health [4,5]. Lifestyle patterns have significant effects on long-term morbidity and mortality that is becoming increasingly evident.…”
Section: Introductionmentioning
confidence: 99%
“…Resultados finales del ajuste de modelos de regresión a los datos sobre determinantes próximos del estilo de vida promotor de salud: Modelo óptimo I N V E S T I G A C I Ó N las muertes y de 43% de la carga de enfermedad global 18 . Se destaca en este estudio que los adultos maduros tienen más altos puntajes de EVPS que los adultos jóvenes y adolescentes, estos hallazgos encuentran apoyo en los estudios que sostienen que el EV parece mejorar con la edad, en respuesta tanto a cambios biológicos como psicosociales [19][20][21][22] . El hecho que se infiera que los adultos maduros son más responsables en salud que los adultos jóvenes, probablemente los adultos maduros están más conscientes de los riesgos que existen para su salud o a que ellos presentan episodios de enfermedad con más frecuencia, lo que los mantiene más en contacto con los sistemas asistenciales como apoyos sociales.…”
Section: Tabla 3 Regresión Bivariada De Cada Factor Del Estudio Con unclassified
“…The HPLP-II is an upgraded version of the HPLP, which has been used extensively in health promotion research [8] and has been reported to have sufficient validity and reliability by various studies that explored the determinants and actual state of a health-promoting lifestyle [9][10][11][12]. In Japan, the Japanese version of the HPLP-II was developed by Wei et al [13], and has been used by many researchers [14].…”
Section: Introductionmentioning
confidence: 99%